Une critique de l’urbain depuis le champ des ambiances - Rachel Thomas (Ambiances)
This prospective article suggests ways of developing a critique of the urban from the field of ambiences. Whilst critique does exist in this field, it is aimed at the field of architecture and design, which is accused of neglecting the sensory dimensions of space. A critique of the urban from the field of ambiences seeks to demonstrate the need to clarify the societal issues related to the planned transformation of urban ambiences. What is the role of ambiences in setting up processes of normalisation of ordinary urban behaviour that can create vulnerability, antisocial behaviour or even forms of exclusion? The central argument of the text is to open up the field of ambiences to closer interactions with the question of political, mainly sensory forms of life. It is a question of grasping the political in ambiences from concrete situations of investigation and from their genealogy, by describing, questioning and appreciating their transformation and their role in the development of plural ways of being, and of being affected.